Reeder and Felson’s Gamuts in Cardiovascular Radiology Comprehensive Lists of Radiographic and Angiographic Differential Diagnosis - Reeder, Maurice M. (Springer New York, 1994)
All the gamuts pertaining to the heart and great vessels have been excerpted from Reeder and Felson's Gamuts in Radiology, the world's best known, most trusted, and most comprehensive guide to radiologic differential diagnosis. The gamuts have been reorganized and renumbered for ease of use. This book is especially useful for residents in cardiology